Вміст вільного проліну при реалізації морфогенетичного потенціалу соняшника за Agrobacterium-опосередкованої трансформації - Комісаренко, А.Г.; Михальська, С.І.; Сергєєва, Л.Є.; Курчій, В.М.; Тищенко, О.М. (Фактори експериментальної еволюції організмів, 2014)
Aim. Plant tissue totipotency – is the essential ability that is used in biotechnology. This peculiar feature responds to various changes of the total metabolism as well as fluctuations of some substances. Proline takes part in diverse functions of the plant both under normal and stress conditions. Proline has a concern in morphogenesis and genetic transformation. The levels of free proline in sunflower tissues with different morphogenetic abilities and in tissues of transformed plant were investigated. Methods. Agrobacterium-mediated transformation with LBA 4404 strain with pBi2E suppressor proline dehydrogenase gene was created. The sunflower transformants were regenerated. The free proline contents were estimated in different tissues of normal and transformed plants. Results. The levels of free proline raise in tissues with high totipotency (initial explants and regenerants at the early stages of morphogenesis). The proline contents in transformed plants exceeded those parameters of controls during whole cultivation in vitro.